KEMAMPUAN MENULIS TEKS NARASI MENGGUNAKAN MEDIA AUDIO VISUALSISWA KELAS VII SMP NEGERI 3 SOLOK SEMESTER 1 TAHUN PELAJARAN 2021/2022 - Annisa Rizkha Desy (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2021)
Based on the results of observations and interviews, the researchers found that writing a narrative was boring for students, so the researchers added Audio Visual media in writing student narrative texts. This type of research is quantitative with the method used in the research method of pre-experimental design with a one-shot case study design. The results of the research that has been carried out can be seen that (1) the students' ability to use the structure before using audio-visual media in writing narrative texts is at a low qualification with an average value of 45.96, after using audiovisual media with structures in writing narrative texts is in good qualification, with an average value of 76.61 (2) the ability of students with linguistic elements before using audio visual media in writing narrative texts is in almost sufficient qualification, with an average value of 50, after using audio visual media with linguistic elements in writing narrative text, the qualification is almost sufficient, with an average score of 55.64 (3) the ability to write narrative text with capital letters and punctuation marks before using audio-visual media is in poor qualification, with an average value of 40.13, after using audio-visual media is in almost sufficient qualification with an average score of 55.65 (4) overall The ability to write narrative texts before using audio-visual media with a sample of 31 students is classified as lacking with an average value of 46.16, after using audio-visual media the students' ability to write narrative texts with a total of 31 students is classified as good, with an average value of an average of 62.93, this value is in the qualification.